Clinical Findings, Treatment and Long-Term Outcome in 37 Cats with Non-Associative Immune-Mediated Hemolytic Anemia: A Retrospective Observational Study of Two Treatment Cohorts - Lisa-Maria Kulmer; Pavlos G. Doulidis; Iwan A. Burgener; Nicole Luckschander-Zeller (Animals, 2026)
Background: Non-associative immune-mediated hemolytic anemia (IMHA) is uncommon in cats and carries substantial mortality. Glucocorticoids are first-line treatment, and cyclosporin A (CsA) is frequently added, but data on the clinical course and long-term outcome are limited. We describe clinical findings, treatment, adverse events and outcome in cats with non-associative IMHA. Methods: In this retrospective observational single-center study (October 2014–October 2024), 37 cats diagnosed by the 2019 ACVIM consensus criteria were included; 15 received prednisolone alone (PG) and 22 prednisolone combined with CsA (CPG), allocated at the clinician’s discretion. Between-cohort comparisons are exploratory. Results: Cats in the CPG cohort presented with more severe anemia. Overall mortality was 24.3%, with all deaths within four weeks; survival to discharge was 13/15 (PG) and 19/22 (CPG). Median follow-up was 50 [8–430] and 70 days [12–330]. Two cats achieved sustained treatment-free remission of 4.2 and 1.9 years. Five cats relapsed, four while receiving ongoing immunosuppression. Conclusions: Most cats survived the acute phase but required prolonged immunosuppression, and sustained treatment-free remission was uncommon. Relapses occurred predominantly during ongoing therapy rather than after discontinuation. Because CsA was used preferentially in more severely affected cats, comparative efficacy cannot be assessed and remains to be addressed prospectively.